Development of Powtoon Animation Video Learning Media on Circle Materials at UPT Senior High School 06 South Solok - Suryani Salfitri; Sofia Edriati; Dewi Yuliana Fitri (Rangkiang Mathematics Journal, 2022)
The research is a research and development that purpose to produce Powtoon animation video learning media on circle material. In addition, this study purpose to determine the validity and practicality of Powtoon animation video learning media on circle material. The development model used is the Plomp model. This learning media was created using the Powtoon application. The instruments used are validity sheets, practicality questionnaires, and interview guidelines to determine the validity and practicality of learning media. Based on the validation results on the development of Powtoon animation video learning media, the percentage is 86,31%. While the results of the practicality of teacher and students obtained a percentage of 93,2%. Thus, the Powtoon animation video learning media on the circle material is declared to be very valid dan very practical to use in learning.